Peningkatan Keterampilan Pengolahan Sabun Cuci Piring Sederhana Untuk Masyarakat Di Desa Rambah Baru - Asiah Wasillah; Almaghfiroh Almaghfiroh; Aulia Putri; Cindy Octavia Putri; Esther Angelita Gurning; MHD.Revaldi; Muhammad Fazlan; Nur Aulia; Sultan Rafliansyah Harahap; Salsa Nurul Fajri; Yogi Yudistira Ade Putra (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Dishwashing soap is a cleaning product that has become a part of everyday life. With the growth of the population and changes in lifestyle, the demand for dishwashing soap continues to rise. This soap plays a crucial role in maintaining cleanliness, which is currently a vital aspect of health. Every homemaker relies on dishwashing soap to clean their kitchen utensils. The purpose of this initiative is to provide training to the local community in the Rambah Baru Village on how to make simple dishwashing soap. During this training, the direct production of liquid dishwashing soap is carried out using the necessary ingredients such as Texapon, Sodium sulfate (Na2SO4), foam booster, EDTA 2Na, NaCl, fragrance essence, and table salt. This production process yields approximately 20 liters of liquid dishwashing soap. Furthermore, this dishwashing soap also holds significant economic value, which can serve as a solution for improving the local economy in the village.